“Marginal” Tangos: Imaginary, Circulation and Interpretation (Revista Argentina de Musicología, 2018)
In the imaginary about tango, the question of its marginal origin appears frequently. The idea that tango arose from “the underworld” (“los bajos fondos”) provokes rejection and attraction with similar intensity from the very beginning. Traditional historiography of the genre reinforces that myth in line with certain lyrics where the “low” environments are recreated. But the exaltation of an idealized past –“he was poor but decent”– contrasts to the complexity of those same poems from which the praise of simplicity is claimed. Likewise the international circulation of scores and records since early Twentieth-Century placed the tango between the core products of the culture industry. Being undeniably popular from the beginning, tango did not take long to become a written music and, in that sense, closer to art music than to the tradition of oral music. The assessment of the performing dimension as a result of the recordings will also promote differentiation between versions, stimulating musicians’ creative search. The tango is a cultural emerging where dichotomous pairs like central-marginal, high-low, local-global, art music-popular music seem insufficient to account for what happens.
Keywords: tango; marginalization; imaginary; circulation; interpretation